Concept Analysis of Post-Stroke Cognitive Function in Ischemic Stroke Patients: Implications for Nursing Practice - Muhammad Ardi; Salim Harris; I Made Kariasa; Bambang Wispriyono (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Ischemic stroke is a major cause of neurological disability, often resulting in cognitive impairment that impacts quality of life, functional status, and caregiver burden. However, there has been no systematic conceptual analysis explaining the attributes, antecedents, and consequences of cognitive function in ischemic stroke patients. Thi study aims to comprehensively analyze the concept of cognitive function in ischemic stroke patients, clarifying its definition, attributes, antecedents, consequences, and empirical references. This concept analysis followed the seven-steps approach by Walker and Avant. Literature search was conducted through PubMed, Scopus, and CINAHL with the following inclusion criteria: publications from 2020 to 2025, in English, focusing on post-stroke cognitive function. A total of 22 articles from various disciplines were analyzed. Empirical references were selected based on their relevance to cognitive attributes. Data were extracted and synthesized according to the attributes, antecedents, and consequences to form a conceptual definition. The six main attributes of cognitive function in ischemic stroke are: memory, executive function, attention, language, orientation, and visuospatial function. Antecedents include biological-structural factors (infarct location/size), sociodemographic factors (age, education), clinical factors (comorbidities, stroke severity), functional factors, and psychological factors. The consequences include a decline in quality of life, functional status, increased caregiver burden, and mortality. Instruments such as MoCA, MMSE, and biological biomarkers were identified as key empirical references. This conceptual analysis provides a strong theoretical foundation for nursing practice, emphasizing the importance of early detection and attribute-based multidisciplinary interventions to prevent further cognitive decline.  This study has limitations, as variations in the assessment phase may affect the heterogeneity of cognitive impairment. Further research is recommended to validate this concept with clinical data, test the effectiveness of specifically designed interventions, and conduct longitudinal studies to monitor long-term cognitive function.